2000
DOI: 10.1021/cm000083i
|View full text |Cite
|
Sign up to set email alerts
|

Infrared and NMR Spectroscopic Studies of n-Alkanethiols Chemically Grafted on Dimethylzinc-Modified Silica Surfaces

Abstract: Transmission infrared and solid-state nuclear magnetic resonance (NMR) spectroscopies are used to study the surface species formed by sequential reaction of hydroxylated, high-surface-area silica with dimethylzinc (DMZ) and n-alkanethiols of various chain lengths. Reaction of DMZ forms mainly surface methylzinc species. These convert to Zn-bound ethanethiolate surface species by reaction with ethane thiol, evolving nearly identical amounts of methane at each step. Temperature-dependent infrared spectra of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Table 1 enables a comparison of spectra observed at different temperatures, along with their assignments. In large agreement with the literature data, [19,20,21,24,26] we are able to draw the following conclusions: DRIFTS spectra of n-decanethiol adsorbed on Ni recorded at four different temperatures, 23°, 700°, 1030°, and 1050°C a) at high frequency and b) at low frequency.…”
Section: Experimental: Materials and Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…Table 1 enables a comparison of spectra observed at different temperatures, along with their assignments. In large agreement with the literature data, [19,20,21,24,26] we are able to draw the following conclusions: DRIFTS spectra of n-decanethiol adsorbed on Ni recorded at four different temperatures, 23°, 700°, 1030°, and 1050°C a) at high frequency and b) at low frequency.…”
Section: Experimental: Materials and Methodssupporting
confidence: 90%
“…(2) The spectrum recorded of the samples treated at 700˚C (exposure of 13 hours at this temperature) and 1030°C shows, besides bands observed at 23°C, the appearance of new bands corresponding to chemical species containing the groups C=C, -C=C=CH 2 , >C=C=CH 2 , and aromatic ring [20,21,24,25 ]. When these surfaces are thermally treated under Ar carrier gas at 1050°C over 6 hours, all previous bands characteristic of the adsorption of n-decanethiol on Ni disappear, and other bands, corresponding to characteristic groups in olefinic or aromatics, or both, compounds [20,21,24,26] appear. In a previous study [19] the authors have shown that the same type nickel powder, impregnated with n-decanethiol, is inactive for the steam reforming of methane, and this deactivation was found to be due to carbon deposition of the "unsaturated" type.…”
Section: Resultsmentioning
confidence: 99%
“…A number of methods have been used to study modified silica surfaces, such as solid-state NMR spectroscopy, atomic force microscopy, Fourier transform infrared spectroscopy, photon correlation spectrometry, thermogravimetric analysis, nitrogen adsorption, X-ray powder diffraction, and rheological measurements . A key disadvantage of many of these methods is the need for large sample sizes or samples with high surface areas, particularly when monolayer or lower coverage of a modifier is present on a silica surface.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the possible assignment of the individual absorption bands to the corresponding bond configuration was undertaken. At low frequencies, the spectrum recorded at 23 • C shows the presence of bands characteristic of n-decanethiol adsorption on Ni (ν(C S), δ(CH 2 ) and δ(CH 3 )), and the presence of sulfonates [37][38][39][40][41]. The IR spectra of the samples tested for methane steam reforming at 700 • C (exposure of 13 h at this temperature) show, in addition to the bands observed at 23 • C, the appearance of new bands, corresponding to characteristic groups of unsaturated compounds [38][39][40][41].…”
Section: Catalytic Testmentioning
confidence: 99%
“…At low frequencies, the spectrum recorded at 23 • C shows the presence of bands characteristic of n-decanethiol adsorption on Ni (ν(C S), δ(CH 2 ) and δ(CH 3 )), and the presence of sulfonates [37][38][39][40][41]. The IR spectra of the samples tested for methane steam reforming at 700 • C (exposure of 13 h at this temperature) show, in addition to the bands observed at 23 • C, the appearance of new bands, corresponding to characteristic groups of unsaturated compounds [38][39][40][41]. At high frequencies, the spectrum recorded at 700 • C shows the presence of bands ν(CH 2 ) and ν(CH 3 ) also present at 25 • C. The presence of the last two bands at 700 • C can be explained as follows: the heating of the decanethiol-impregnated Ni powder up to 700 • C during the reaction of steam reforming is characterized by the partial pyrolysis of the adsorbed layers.…”
Section: Catalytic Testmentioning
confidence: 99%